A variant of human paraoxonase/arylesterase (HUMPONA) gene is a risk factor for coronary artery disease. - Serrato, M (1995)
Coronary artery disease (CAD) is a complex trait caused by a number of genetic and environmental factors. Recently, paraoxonase/arylesterase (PONA) enzyme has been implicated in the pathogenesis of atherosclerosis. There is a 10-40-fold variability in the activity of this enzyme among individuals. This variability is due to the presence of an A/G polymorphism in the coding region of the gene (HUMPONA). The A and G alleles code for glutamine (A genotype) and arginine (B genotype), respectively. Individuals with A genotype have a lower enzymatic activity than those with B genotype. We determined the HUMPONA genotypes and alleles in 223 patients with angiographically documented CAD and in 247 individuals in the general population. The distribution of genotypes were in Hardy-Weinberg equilibrium in patients and in controls. Genotypes A and B were present in 120 (49%) and 28 (11%) individuals in controls and in 68 (30%) and 40 (18%) patients with CAD, respectively (chi squared= 16.5, P= 0.0003). The frequency of the A allele was 0.69 in controls and 0.56 in patients (OR= 1.7, P= 0.0001). There were no differences in the distribution of HUMPONA genotypes in the subgroups of patients with restenosis, myocardial infarction, or any of the conventional risk factors for CAD as compared with corresponding subgroups. In summary, variants of the HUMPONA gene are involved in predisposition to coronary atherosclerosis.